The 6-PACK programme to decrease falls and fall-related injuries in acute hospitals: protocol for an economic evaluation alongside a cluster randomised controlled trial - Morello, R.; Barker, A.; Zavarsek, S.; Watts, J.; Haines, T.; Hill, Keith; Sherrington, C.; Brand, C.; Jolley, D.; Stoelwinder, J. (2012)
Falls are a common hospital occurrence complicating the care of patients. From an economic perspective, the impact of in-hospital falls and related injuries is substantial. However, few studies have examined the economic implications of falls prevention interventions in an acute care setting. The 6-PACK programme is a targeted nurse delivered falls prevention programme designed specifically for acute hospital wards. It includes a risk assessment tool and six simple strategies that nurses apply to patients classified as high-risk by the tool. To examine the incremental cost-effectiveness of the 6-PACK programme for the prevention of falls and fall-related injuries, compared with usual care practice, from an acute hospital perspective. The 6-PACK project is a multicentre cluster randomised controlled trial (RCT) that includes 24 acute medical and surgical wards from six hospitals in Australia to investigate the efficacy of the 6-PACK programme. This economic evaluation will be conducted alongside the 6-PACK cluster RCT. Outcome and hospitalisation cost data will be prospectively collected on approximately 16,000 patients admitted to the participating wards during the 12-month trial period. The results of the economic evaluation will be expressed as 'cost or saving per fall prevented' and 'cost or saving per fall-related injury prevented' calculated from differences in mean costs and effects in the intervention and control groups, to generate an incremental cost-effectiveness ratio (ICER). This economic evaluation will provide an opportunity to explore the cost-effectiveness of a targeted nurse delivered falls prevention programme for reducing in-hospital falls and fall-related injuries. This protocol provides a detailed statement of a planned economic evaluation conducted alongside a cluster RCT to investigate the efficacy of the 6-PACK programme to prevent falls and fall-related injuries. The protocol for the cluster RCT is registered with the Australian New Zealand Clinical Trials Registry (ACTRN12611000332921).